Stigma and burden of mental illness and their correlates among family caregivers of mentally ill patients - Omnya S. Ebrahim; Ghada S. T. Al-Attar; Romany H. Gabra; Doaa M. M. Osman (Journal of the Egyptian Public Health Association, 2020)
Abstract Background and objectives Family caregivers play a curial role in supporting and caring for their mentally ill relatives. Their struggle for facing stigma and shouldering caregiving burden is marginalized, undervalued, and invisible to medical services. This study assessed the stigma and burden of mental illnesses, and their correlates among family caregivers of mentally ill patients. Methods A cross-sectional study design was used to collect data from 425 main family caregivers of mentally ill patients at Assiut University Hospital. A structured interview questionnaire was designed to collect socio-demographic data of both patients and their caregivers. Stigma scale for caregivers of people with mental illness (CPMI) was used to assess the affiliate stigma, while the associative stigma was assessed by the explanatory model interview catalogue stigma scale (EMIC-Stigma scale). The caregivers’ burden was assessed using Zarit burden Interview, and Modified Attitude toward Mental Illness Questionnaire was used to assess caregivers’ knowledge and attitude towards mental illness. Results Bipolar disorder (48%) and schizophrenia/other related psychotic disorders (42.8%) were the most common mental illnesses among the study patients. The mean scores of CPMI total scale, EMIC-Stigma scale, and Zarit Burden scale were 56.80 ± 7.99, 13.81 ± 5.42, and 55.20 ± 9.82, respectively. The significant correlates for affiliate stigma were being parents of patients (ß = 4.529, p < 0.001), having higher associate stigma (ß = 0.793, p < 0.001), and aggressive behavior of mentally ill patients (ß = 1.343, p = 0.038). The significant correlates for associate stigma of the study caregivers were being caregivers’ relatives other than parents (ß = 1.815, p = 0.006), having high affiliate stigma (ß = 0.431, p < 0.001), having poor knowledge and negative attitude towards mental illness (ß = − 0.158, p = 0.002), and aggressive behavior of mentally ill relatives (ß = 1.332, p = 0.005). The correlates for the high burden were ...